2018
DOI: 10.3390/polym10111268
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phosphated K-Carrageenan and Its Application for Flame-Retardant Waterborne Epoxy

Abstract: In this paper, phosphated K-carrageenan (P-KC) was obtained by reacting POCl3 with the renewable source K-carrageenan (KC). P-KC and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) were added into waterborne epoxy (EP) to improve its flame retardancy. The structure of P-KC was studied comprehensively using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), thermo-gravimetric analysis (TGA), showing the successful synthesis of P-KC. The flame retardancy of the EP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Hollow symbols are indicative of fiber-incorporated composites with details earlier given in the bottom of Table 1 as a to l notes. Here: FP1-4, FP1-6, FP1-8 [24], DPO-PHE-11.68, DOPO-PHE-12.03 [25], DOPO-T-2.34, DOPO-T-4.67, DOPO-T-6.99, DOPO-T-9.34 [26], AEPP-5, AEPP-10, AEPP-15 [27], DiDOPO-3 [28], DiDOPO-10, DiDOPO-11 [29], DiDOPO-7 [30], DiDOPO-1, DiDOPO-5, DiDOPO-10 [31], DiDOPO-1, DiDOPO-5, DiDOPO-10, DiDOPO-15, DiDOPO-20 [32], PPMS-15, PPMS-EG-15 [33], PPMS-MWCNT-5, PPMS-MWCNT-10, PPMS-MWCNT-15, PPMS-15 [34], DPIPP-7.5, DPIPP-15, DPPIO-7.5, DPPIO-15 [35], IDOP-5, IDOP-10, IDOP-15 [36], PPAP-5 [37], AlPBu-10, AlPBu-11, AlPBu-12 [38], MPL-DOPO-2.5, MPL-DOPO-5, DDM-DOPO-2.5, DDM-DOPO-5 [39], ATZ-6 [40], P-KC-30, DOPO-30 [41], DHPP-OH-BAC-5, DHPP-OH-BAC-10, DHPP-OH-BAC-15 [42], PPAP-5, PPAP-10, PPAP-20 [43], [Dmim]Tos-2.4, [Dmim]Tos-4, [Dmim]Tos-7.5 [44], MPhP-10, MPhP-15, MPhP-20 [45], MDOP-0.96, MDOP-1.9, MDOP-3.75, MDOP-7.24 [46], AlPi-7, MPP-7 [47], A-BP-9 [48], CLEP–DOPO–POSS-2.91 [19], CuPP-1, CuPP-2, CuPP-4, CuPP-6, CuPP-8 [49], DOP-ABZ-15, DOP-ABZ-17.5, DOP-ABZ-20 [50], DOPO-7.11, BPD-3.38, BPD-6.71, BPD-10.04, BPD-13.41 […”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Hollow symbols are indicative of fiber-incorporated composites with details earlier given in the bottom of Table 1 as a to l notes. Here: FP1-4, FP1-6, FP1-8 [24], DPO-PHE-11.68, DOPO-PHE-12.03 [25], DOPO-T-2.34, DOPO-T-4.67, DOPO-T-6.99, DOPO-T-9.34 [26], AEPP-5, AEPP-10, AEPP-15 [27], DiDOPO-3 [28], DiDOPO-10, DiDOPO-11 [29], DiDOPO-7 [30], DiDOPO-1, DiDOPO-5, DiDOPO-10 [31], DiDOPO-1, DiDOPO-5, DiDOPO-10, DiDOPO-15, DiDOPO-20 [32], PPMS-15, PPMS-EG-15 [33], PPMS-MWCNT-5, PPMS-MWCNT-10, PPMS-MWCNT-15, PPMS-15 [34], DPIPP-7.5, DPIPP-15, DPPIO-7.5, DPPIO-15 [35], IDOP-5, IDOP-10, IDOP-15 [36], PPAP-5 [37], AlPBu-10, AlPBu-11, AlPBu-12 [38], MPL-DOPO-2.5, MPL-DOPO-5, DDM-DOPO-2.5, DDM-DOPO-5 [39], ATZ-6 [40], P-KC-30, DOPO-30 [41], DHPP-OH-BAC-5, DHPP-OH-BAC-10, DHPP-OH-BAC-15 [42], PPAP-5, PPAP-10, PPAP-20 [43], [Dmim]Tos-2.4, [Dmim]Tos-4, [Dmim]Tos-7.5 [44], MPhP-10, MPhP-15, MPhP-20 [45], MDOP-0.96, MDOP-1.9, MDOP-3.75, MDOP-7.24 [46], AlPi-7, MPP-7 [47], A-BP-9 [48], CLEP–DOPO–POSS-2.91 [19], CuPP-1, CuPP-2, CuPP-4, CuPP-6, CuPP-8 [49], DOP-ABZ-15, DOP-ABZ-17.5, DOP-ABZ-20 [50], DOPO-7.11, BPD-3.38, BPD-6.71, BPD-10.04, BPD-13.41 […”
Section: Figurementioning
confidence: 99%
“…Hollow symbols are indicative of fiber-incorporated composites with details earlier given in the bottom of Table 1 as notes a to i . Here: DiDOPO-1.5/GN-1.5 [28], DiDOPO-10/MWCNT-0.8 [29], DiDOPO-3.5/OMMT-3.5 [30], DiDOPO-0.5/OLDH-0.5, DiDOPO-2.5/OLDH-2.5, DiDOPO-5/OLDH-5 [31], IFR-40, IFR-39/CES-1, IFR-38/CES-2, IFR-37/CES-3, IFR-35/CES-5 [208], DOPO-15/P-KC-15, DOPO-20/P-KC-10, DOPO-25/P-KC-5 [41], mAPP-5/PER-5, mAPP-5/RCC-5, mAPP-5/ORCC-5 [209], PEPA–TMA-12/MCA-6, PEPA–TMA-16/MCA-8, PEPA–TMA-20/MCA-10 [210], ZIF8-1/MgAl-LDH-1, ZIF67-1/MgAl-LDH-1 [170], TAT-18/DOPO-2, TAT-16/DOPO-4, TAT-14/DOPO-6, TAT-12/DOPO-8, TAT-18/HPCP-2, TAT-16/HPCP-4, TAT-14/HPCP-6, TAT-12/HPCP-8 [52], EDA-APP-19/Cu 2 O-2 [55], CP-6B-3/MH-0.5 [56], IFR-20, IFR-19.5/HGM-0.5, IFR-19/HGM-1, IFR-18/HGM-2, IFR-16/HGM-4 [211], APP-5/PSA-5 [58], MFAPP-6.25/PER-6.25, MFAPP-6.25/ST-6.25, MFAPP-6.25/OST-6.25 [212], EG-16/DOPO-4, EG-14/DOPO-6, EG-12/DOPO-8, EG-10/DOPO-10, EG-16/HPCP-4, EG-14/HPCP-6, EG-12/HPCP-8, EG-10/HPCP-10 [66], TMT-8.3/DOPO-2.7, TMT-8.2/DOPO-4.1, TMT-8.1/DOPO-5.6, TMT-8/DOPO-7 [67], DOPO-3/APHP-3, DOPO-4/APHP-2 [75], TAD-4/OMMT-1 [77], FR-20/APP-10, FR-15/APP-15, FR-12/APP-18, FR-10/APP-20 [213], ATCP-15/FRHA-1, ATCP-15/FRHA-3, ATCP-15/FRHA-5 [89], ATCP-15/FRHA-1, ATCP-15/FRHA-3, ATCP-15/FRHA-5 [90], APP-4/MMT-6 [93], DOPO-5/MMT-1 [94], BDP-6.7/PHP-3.3 [95], OPS-2.5/DOPO-2.5 [102], …”
Section: Figurementioning
confidence: 99%
“…Figure 3 presents the TG and DTG curves of KC and KC–Fe under N 2 . As shown in the figure, the mass loss of KC before 150 °C was due to the thermal evaporation of intramolecular bound water [27]. KC decomposed in two steps between 150 and 800 °C and the two peaks related to the maximum degradation rate exhibited on the DTG curve appeared at 154 and 708 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the preliminary work of our group, it was found that the bio-based material k-carrageenan was an excellent flame retardant [27,28]. Therefore, in order to further improve its smoke suppression performance, the k-carrageenan–iron complex (KC–Fe) was obtained by grafting a carrageenan molecule with the transition metal element Fe through a complexation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…All achieved UL-94 V0 ratings, except for the marked ones. 1, 11, 12, 14, 16, 20, 32, 33 = DOPO [133,[144][145][146][147][148][149][150] ; 2 = DOPO-PHE (PHE = bis[4-hydroxyphenyl] methyl) diphenylphosphine oxide) [151] ; 3 = DOPO-T (T = cyanuric chloride). [152] 4,5,6,7,8 = DiDOPO (phenethyl-bridged DOPO derivative) [76,[153][154][155] ; 9 = DOPO-MPL (MPL = 6-morpholino-6Hdibenzo[c,e][1,2]oxaphosphinine 6-oxide) [156] ; 10 = DOPO-ATZ (ATZ = 6-(([1H-tetrazol-5-yl]amino)(4hydroxyphenyl)methyl) dibenzo[c,e] [1,2] oxaphosphinine 6-oxide) [58] ; 13 = DOPO-BPD (BPD = 1,4-Phthalaldehyde & 2-benzothiazolamine) [145] ; 15 = DOPO-TPMP (TPMP = reaction between 4-(hydroxymethyl)-2,6,7-trioxa-1-phosphabicyclo[2.2.2]octane 1-oxide and 6-(2,5-dihydroxyphenyl)-6H-dibenzo[c,e][1,2]oxaphosphinine 6-oxide) [157] ; 17 = DOPO-PEPA (PEPA = 1-oxo-4-hydroxymethyl-2,6,7-trioxa-l phosphabicyclo[2.2.2] octane) [147] ; 18 = DOPO-BNP (BNP = phenylboronic acid) [158] ; 19 = DOPO-DTB (DTB = reaction between triglycidyl isocyanurate & DOPO & boric acid) [159] ; 21 = DOPO-TMT (TMT = tri[phosphaphenanthrenemaleimide-phenoxyl]-triazine) [148] ; 22 = D-bp (bp = reacted 4,4 0diaminodiphenyl methane & 4-hydroxybenzaldehyde) [160] ; 23 = DOPO = TAD (TAD = triallyl isocyanurate) [161] ; 24 = DOPOtrif (trif = tri-(phosphaphenanthrene-[hydroxyl-methylene]phenoxyl)-1, 3, 5-triazine) [162] ; 25 = DOPO-TOD (TOD = reacted with 1,3,5-triglycidyl isocyanurate & 10-(2,5-dihydroxyphenyl)-10-H-9-oxa-10-phosphaphenanthrene10-oxide) [163] ; 26 = DOPO-DDM (DDM = 4,4diaminodiphenyl methane) [164] ; 27 = DOPO-DDE (DDE = 4,4diaminodiphenyl ether) [164] ; 28 = DOPO-DDS (DDS = 4,4-diaminodiphenyl sulfone) [164] ; 29 = DOPO-ABZ (ABZ = 2-aminobenzothiazole) [165] ; 30 = DOPO-MMT (MMT = montmorillonite)…”
Section: Layered Silicatesmentioning
confidence: 99%